Dietary Impact on Postprandial Lipemia - Bozzetto, Lutgarda; Della Pepa, Giuseppe; Vetrani, Claudia; Rivellese, Angela Albarosa (Frontiers in Endocrinology, 2020)
Abnormalities in postprandial lipemia (PPL), particularly those related to triglyceride-rich lipoproteins, are considered an independent cardiovascular risk factor. As diet is known to be one of the main modulators of PPL, the aim of this review was to summarize and discuss current knowledge on the impact of diet and its components on PPL in humans; specifically, the impact of weight loss, different nutrients (quantity and quality of dietary fats, carbohydrates, and proteins), alcohol and other bioactive dietary components (i.e., polyphenols), as well as the effect of different dietary patterns. The possible mechanisms behind the metabolic effects of each dietary component were also discussed.